Limniris blueflag in the conditions of Sochi Black Sea region - V. V. Kozina; N. A. Slepchenko; K. V. Klemeshova (Новые технологии, 2017)
In the conditions of the Sochi Black Sea region representatives of Blueflag species from the Limniris subgenus - Iris pseudacorus and I. sibirica begin to vegetate in the first decade of February and the second decade of March, respectively. Decorativeness is preserved for a long time- up to 250 days (I. sibirica) and 306 days (I. pseudacorus). They have high decorative qualities. The intensity of vegetative reproduction, as well as the ability to seed reproduction of the studied species, indicates adaptation to new conditions of cultivation.